(untitled) (CIPEEX, 2025)
Abstract This experience report describes the implementation of an operative group on workplace harassment with workers from NASSA (Occupational Health Support Center of Anápolis), developed by Group 4 of the PET-Health Equity Program. The objective was to promote critical reflection on different forms of harassment — moral, sexual, virtual, school-related, and discriminatory — through participatory activities that stimulated dialogue, the sharing of experiences, and the construction of collective coping strategies. The method followed a structured script in five stages: welcoming, integration activity, conceptual presentation with contextualized examples, discussion circle guided by key questions, and presentation of institutional channels for reporting and prevention. A preliminary rehearsal with the PET- Health team allowed adjustments in clarity, timing, and appropriateness of the conduction. The results indicated increased awareness of the impacts of harassment on personal and professional life, strengthening of collective dialogue spaces, and appreciation of institutional equity policies. It is concluded that the operative group constituted a mobilizing practice, with the potential to empower workers and contribute to critical training in occupational health and health education. Keywords: Moral Harassment; Sexual Harassment; Occupational Health; Health Equity; Health Education